Virgil's Non-linear Narrative and His Aeneids's Two Voices - Schade, Gerson (2018)
Half a century ago American scholars thought to discern two voices while reading the Aeneid, a private one of regret and doubt, a public one of triumph and glory. Since the Aeneid’s narrative is defined by two parallels, however, one looking backward, between Aeneas and Achilles, and another looking forward, between Aeneas and Augustus, one may ask various questions. Did Augustus enjoy being portrayed as such a double-bind hero as Aeneas? Or, did he let it pass only because Virgil was close to him? Friendship, indeed, plays a major role in the Aeneid. Moreover, it may determine one’s survival, as the case of Virgil’s friend Gallus, who held a very special place in Virgil’s poetry before his Aeneid, shows. Actually, what is his new type of poetry, which attracted T.S. Eliot? What is so new in it, and is it really a “Christianised” reading as the detractors of Eliot claim which still makes the Aeneid such an inspiring text? Is it not the feeling that we no longer, or not only, hear about superhuman heroes from bygone eras but actually, or also, listen to human beings, see how their conflicts develop and how they are partially but only unsatisfactorily solved? The starting point is “Actium”, shorthand for Octavian’s war with Antony and Cleopatra, which establishes the Aeneid’s crucial parallel between Aeneas and Augustus.
Keywords: narrative